2020
DOI: 10.17533/udea.rccp.v33n1a02
|View full text |Cite
|
Sign up to set email alerts
|

Dietary addition of curcumin favors weight gain and has antioxidant, antiinflammatory and anticoccidial action in dairy calves

Abstract: Background: Curcumin has been used as an additive in the diet of animals in recent years due to the potent medicinal properties of this molecule. Objective: To evaluate whether the addition of curcumin to the diet of calves at different phases (pre- and post-weaning) has a positive effect on metabolic profile, performance, and anti-coccidian action. Methods: Thirtythree Holstein calves were selected at various phases of development: Experiment 1 (E1: n=10) 18±7 (pre-weaning), Experiment 2 (E2: n=11) 64±4 (pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
1
0
2
Order By: Relevance
“…kurkumin kullanımı ile koksidiyozise bağlı intestinal lezyonların azalması, antimikrobiyal aktivite, sığırlarda rumen florasında ve nitrojen metabolizmasındaki değişimler kurkuminin ince bağırsaklar hatta ön midelere dahi ulaştığının kanıtlarıdır. [19][20][21] Kurkuminin insan Caco-2 hücre serileri kullanılarak intestinal kanalda dağılımına ait permeabilite testleri göstermektedir ki; apikalden bazolaterale oldukça düşük (%0-20 arası) oral biyoyararlanım söz konusudur. 22,23 Yine diğer Caco-2 hücre serileri kullanılarak yapılan araştırmalarda her iki yönde de (apikalden bazolaterale, bazolateralden apikale) belirgin katsayılar saptanmış, kurkuminin zayıf oral biyoyararlanımı kanıta dayalı olarak sunulmuştur.…”
Section: Buzağılardaunclassified
“…kurkumin kullanımı ile koksidiyozise bağlı intestinal lezyonların azalması, antimikrobiyal aktivite, sığırlarda rumen florasında ve nitrojen metabolizmasındaki değişimler kurkuminin ince bağırsaklar hatta ön midelere dahi ulaştığının kanıtlarıdır. [19][20][21] Kurkuminin insan Caco-2 hücre serileri kullanılarak intestinal kanalda dağılımına ait permeabilite testleri göstermektedir ki; apikalden bazolaterale oldukça düşük (%0-20 arası) oral biyoyararlanım söz konusudur. 22,23 Yine diğer Caco-2 hücre serileri kullanılarak yapılan araştırmalarda her iki yönde de (apikalden bazolaterale, bazolateralden apikale) belirgin katsayılar saptanmış, kurkuminin zayıf oral biyoyararlanımı kanıta dayalı olarak sunulmuştur.…”
Section: Buzağılardaunclassified
“…Kurkumin dalam pakan memiliki aktivitas antioksidan dan antiinflamasi, sehingga mengurangi stres oksidatif dan kinerja produksi domba perah yang lebih baik (Jaguezeski et al, 2018). Menurut Glombowsky et al, (2020) penambahan kurkumin dalam pakan meningkatkan kecernaan pakan dan mengurangi jumlah lesi usus yang disebabkan oleh koksidiosis pada sapi perah. Selain itu, penambahan kadar kurkumin 0,2% dalam konsentrat dapat meningkatkan jumlah bakteri total dan menurunkan jumlah protozoa total pada sapi potong (Vorlaphim et al, 2011).…”
Section: Kecernaan Zat Makananunclassified
“…It also prevents the occurrence of Megaloblastic anemia in animals [18]. A study indicated an increase in the vitality of lambs treated with folic acid, in addition to an increase in the numbers of red and white blood cells, hemoglobin and the level of immunoglobulins in the blood [19].…”
Section: Introductionmentioning
confidence: 99%